Thoraco-abdominal aorta surgical and anesthetic management - Chiesa, Roberto; Melissano, Germano; Zangrillo, Alberto; Coselli, Joseph S. (Springer, 2011)
The thoraco-abdominal aortic pathology is not uncommon and represents the ultimate challenge for vascular surgeons. Written by internationally renowned experts in vascular and cardiac surgery, in anesthesiology and in radiology, the volume  deals with the newest endovascular and hybrid approaches, together with more traditional surgical strategies. It is enriched by several figures illustrating the most important diagnostic findings and depicting key techniques and strategies, thus providing a very practical approach to the main problems encountered from diagnosis to postoperative care. Vascular and cardiac surgeons, anesthesiologists, perfusionists and radiologists will find in this volume useful and updated information for the treatment of this very challenging condition.